Perencanaan dan Perancangan Eco Lakeside Glamping (Glamour Camping) di Kecamatan Kintamani, Bangli - Kadek Putra Mahendra; I Nyoman Gede Maha Putra; A. A. Gede Raka Gunawarman (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
The development of Glamping accommodation into one type of creative tourist accommodation and has become a trend in recent years. Glamping is created from the saturation of tourist accommodation with the desire to experience the outdoors or camping by paying attention to user comfort and the necessary facilities without losing the meaning of camping itself. owned by Kintamani. The increase in tourist accommodation in Bali, especially Kintamani every year is balanced with environmental destruction, so Glamping accommodation is the right choice. Besides that, with the potential that Kintamani has with natural beauty that is in great demand, one of which is Lake Batur itself which is in Kintamani able to provide added value to enjoy glamping accommodation, but in its design later the cold climate and existing topography are important points that must be considered.